Pyruvate Kinase Deficiency in Sub-Saharan Africa - Machado, Patrícia (2021)
Background: Pyruvate kinase (PK) deficiency, causing hemolytic anemia, has been associated to malaria protection and its prevalence in sub-Saharan Africa is not known so far. This work shows the results of a study undertaken to determine PK deficiency occurrence in some sub-Saharan African countries, as well as finding a prevalent PK variant underlying this deficiency. Materials and Methods: Blood samples of individuals from four malaria endemic countries (Mozambique, Angola, Equatorial Guinea and Sao Tome and Principe) were analyzed in order to determine PK deficiency occurrence and detect any possible high frequent PK variant mutation. The association between this mutation and malaria was ascertained through association studies involving sample groups from individuals showing different malaria infection and outcome status. Results: The percentage of individuals showing a reduced PK activity in Maputo was 4.1% and the missense mutation G829A (Glu277Lys) in the PKLR gene (only identified in three individuals worldwide to date) was identified in a high frequency. Heterozygous carrier frequency was between 6.7% and 2.6%. A significant association was not detected between either PK reduced activity or allele 829A frequency and malaria infection and outcome, although the variant was more frequent among individuals with uncomplicated malaria. Conclusions: This was the first study on the occurrence of PK deficiency in several areas of Africa. A common PKLR mutation G829A (Glu277Lys) was identified. A global geographical co-distribution between malaria and high frequency of PK deficiency seems to occur suggesting that malaria may be a selective force raising the frequency of this 277Lys variant.